ʾA khyacʻ naiʹ cacʻ sāʺ - Soṅʻʺ Ve Ūʺ. (Ranʻ kunʻ : Mra Ratanā Cā pe, 2008)
Thirteen short stories about the love lives of soldiers based upon the author's personal experiences in the Tatmadaw.
Author: Thaung Wai Oo, a retired colonel from the Myanmar armed forces
Includes bibliographical references (p. 343)
In Burmese
Keywords: Burma -- Tapʻ ma toʻ -- Military life; Armies -- Burma; Soldiers -- Burma; Burmese fiction; Burma -- Armed Forces